Rumpfmuskelkraft bei Profivolleyballspielern - Miltner, O.; Tschaepe, R.; Weihe, W.; Heinzinger, A.; Kieffer, O. (Sport-Orthopädie - Sport-Traumatologie, 2008)
Due to theVolleyball specific requirement profile core stabilization and trunk strength is a matter of utmost importance.Spine injuries resp.spine and back overloading disorders are common reasons for training and match failures of Volleyball players.In terms of injury prevention and performance enhancement an adequate strength level and muscular balances have to be considered as a major requirement.However there are no accordant volleyball specific data available up to now.Within the scope of an entire preventive assessment the present study collected isometric strength data of 12 male professional volleyball players (German first league) in 3 movement planes.The results of the functional analysis of trunk performance are showing a characteristic performance profile for the team players.Insome of the tested movement patterns the players reached values above there reference values of untrained persons,in other patterns deficits could be analyzed. Regarding muscular balances several players showed imbalances,whether in Flexion/Extension ration or in Rotation/Lateral flexion left and right ratio. Based on the test results individual training recommendations were given to the players.From a sportsmedicine view a detailed analysis of trunk performance and spine strength level before season and the systematic transfer of these data into an according training program are essential prevention measures to forestall injuries and overloading problems in professional Volleyball players.